Heavy metals status in sediment at Can Gio mangrove, Ho Chi Minh city, Vietnam - Phuong, Pham Kim; Tu, Nguyen Dinh; Thanh, Nguyen Vu (Academia Journal of Biology, 2012)
The two field surveys have been organized by the Department of Nematology, Institute of Ecology and Biological resources in the Can Gio mangrove forest, Ho Chi Minh city in the period November 2005 (wet season) and April (dry season) 2006. Some heavy metals in Can Gio mangrove forest sediments such as Cr, Pb, As, Cu and Zn were found in all samples and in both seasons with their concentrations were often higher in dry season. In addition, in dry season some heavy metals such as Cr, As and Oil and Clo originated pestisides were occurred with highest concentrations in the core zone 2 and Thi Vai river area. Cd component was not detected in the dry season (April, 2006), but it was found in the rain season (November, 2005) with concentrations ranged from 6.1 to 7.7 mg/kg. Although the observed heavy metals concentrations are lower than the Vietnam Standard Criteria and indicated the sediments of Can Gio mangrove forest were not too much polluted, however the presence of these heavy metals in sediment of Can Gio Mangrove forest could cause the bio-accumilation for zoobenthos associated with webfood chains in their related ecological system.